The effect of locomotive syndrome on the trajectory of sleep disturbance in geriatric oncology inpatients - Yang, Yu-Ling; Su, Hui; Lu, Hui; Wang, Jing; Zhou, Yu-Qing; Li, Ling; Yu, Hui; Lv, Yan; Chen, Ying (Frontiers in Oncology, 2025)
ObjectiveTo explore the developmental trajectory of sleep disturbance in geriatric oncology inpatients and assess the impact of locomotive syndrome (LS) on this trajectory.MethodsThis longitudinal study enrolled 284 geriatric oncology inpatients through convenience sampling from August 2023 to February 2024 at the Oncology Center of the Affiliated Hospital of Jiangnan University, Wuxi, Jiangsu Province, China. Sleep quality was monitored for seven days following admission (T0-T6) using a wrist motion analyzer. The developmental trajectory of sleep disturbance was analyzed using the latent category growth model (LCGM). Patients were categorized into the LS group (n=177) and the non-LS group (n=107) based on the 25-question Geriatric Locomotive Function Scale (GLFS-25). Comparisons were made between the two groups regarding the distribution of sleep disturbance trajectories.ResultsThree potential categories for the development trajectory of sleep disturbance in inpatients were identified: non-sleep disturbance, sleep disturbance improvement, and sleep disturbance persistence. The lowest sleep quality was observed on the second day after admission (T2). In the non-LS group, 40 cases (37.4%) experienced no sleep disturbance, 45 cases (42.1%) showed improvement, and 22 cases (20.6%) showed persistence of sleep disturbance. In the LS group, 32 cases (18.1%) experienced no sleep disturbance, 50 cases (28.2%) showed improvement, and 95 cases (53.7%) exhibited persistent sleep disturbance. Significant differences were found in the trajectory distribution of sleep disturbance between the two groups (P<0.001).ConclusionsSleep disturbance is prevalent in geriatric oncology inpatients, with an incidence of 74.6% (212/284), and is most severe on the third day after admission. Patients with LS exhibit lower overall sleep quality and a higher likelihood of persistent sleep disturbances.